An Analysis of Purchase Behavior of Generation Y in Kenya - Musyoka, Raymond; Ng’ang’a, Rahab Mugure; Wambugu, Hannah Wanjiku (International Journal of Business, Economics and Management, 2015)
Due to the unique buying behavior of Generation Y, it has become a target of research in developed and emerging markets. This is because, Generation Y comprises of a large demographic segment of consumers with high spending power. Despite this, the buying behavior of Generation Y is not well understood in Kenya. The buying behaviors of Generation Y in developed and emerging markets cannot be applied in developing countries like Kenya, given that factors considered important by Kenya’s Generation Y when making purchase decisions might be different from those in emerging and developed markets. The purpose of this study was to analyze the factors considered important when generation Y in Kenya is making a purchase decision. This knowledge is important because it could influence the marketing strategies of manufacturing firms in Kenyan market. A random sample 1000 generation Y individuals was used, and their feelings about importance of each factor was rated using a Likert scale. Interviews were conducted using a structured questionnaire, and data was analyzed using descriptive statistics. Results indicated that generation Y in Kenya considers quality, price and durability of the product, efficiency and performance of brand, discounts offered and the company when selecting products/brands. The results further indicated that Generation Y got information when making purchase decision from testing and using the product (experience), friends and internet. It was also evident that respondents will recommend the same brand/product to another person and they make a repeat purchase of the same brand when satisfied after using a product. When dissatisfied with a product/service purchased, most of Generation Y consumers will switch to another brand and grumble to friends and relatives. Generation Y in Kenya considers investing in a business, buying a mobile phone and buying a laptop when they have extra cash as very important.